2014
DOI: 10.2139/ssrn.2464513
|View full text |Cite
|
Sign up to set email alerts
|

Management Incentives Under Formula Apportionment Tax-Induced Distortions of Effort and Compensation in a Principal-Agent Setting

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…For example, in the situation where every EU Member State can apply for its own tax rate, the incorporation of payroll costs in the allocation formula will affect employment between the EU Member States. This was proved by Martini et al (2014), who consider a principal agent model of the LEN-type 2 with agents in two different jurisdiction and the allocation formula with the payroll as the only formula factor. They concluded that the employment is shifted to the low tax jurisdiction and the extension of the shifting activities intensifies with the rising tax rate differential.…”
Section: Doi: 1017221/222/2015-agriceconmentioning
confidence: 97%
“…For example, in the situation where every EU Member State can apply for its own tax rate, the incorporation of payroll costs in the allocation formula will affect employment between the EU Member States. This was proved by Martini et al (2014), who consider a principal agent model of the LEN-type 2 with agents in two different jurisdiction and the allocation formula with the payroll as the only formula factor. They concluded that the employment is shifted to the low tax jurisdiction and the extension of the shifting activities intensifies with the rising tax rate differential.…”
Section: Doi: 1017221/222/2015-agriceconmentioning
confidence: 97%